Unenhanced Dynamic MR Angiography: High Spatial and Temporal Resolution by Using True FISP–based Spin Tagging with Alternating Radiofrequency(1) - Yan, Lirong (Radiological Society of North America, Inc., 2010)
PURPOSE: To present an unenhanced four-dimensional time-resolved dynamic magnetic resonance (MR) angiography technique with true fast imaging with steady-state precession–based spin tagging with alternating radiofrequency (STAR), also called TrueSTAR. MATERIALS AND METHODS: This study received Institutional Review Board approval and was HIPAA compliant. Informed consent was obtained from all study subjects. In eight healthy volunteers, the spatial and temporal resolution of the TrueSTAR technique were optimized. In another six healthy volunteers, the contrast-to-noise ratio (CNR) and signal-to-noise ratio (SNR) of the TrueSTAR dynamic MR angiography images were compared with those acquired by using a standard Look-Locker echo-planar technique by using the Wilcoxon signed rank test. Finally, one patient with an arteriovenous malformation (AVM) was studied by using this technique. RESULTS: The SNR and CNR of the TrueSTAR dynamic MR angiography images were 29% and 39% higher, respectively, compared with those acquired by using a standard Look-Locker echo-planar imaging sequence (both P = .028). In the AVM patient, TrueSTAR dynamic MR angiography delineated the dynamic course of labeled blood flowing through feeding arteries into the nidus and draining veins. CONCLUSION: The results suggest that TrueSTAR is a promising unenhanced dynamic MR angiography technique for clinical evaluation of cerebrovascular disorders such as AVM, steno-occlusive disease, and aneurysm. © RSNA, 2010 Supplemental material: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.10091543/-/DC1